Association of industry sponsorship and positive outcome in randomised controlled trials in general and abdominal surgery: protocol for a systematic review and empirical study - Probst, Pascal; Grummich, Kathrin; Ulrich, Alexis; Büchler, Markus W.; Knebel, Phillip; Diener, Markus K. (Systematic Reviews, 2014)
Industry sponsorship has been identified as a factor correlating with positive research findings in several fields of medical science. To date, the influence of industry sponsorship in general and abdominal surgery has not been fully studied. This protocol describes the rationale and planned conduct of a systematic review to determine the association between industry sponsorship and positive outcome in randomised controlled trials in general and abdominal surgery.
Gesehen am 20.10.2020